"Closer to God": Following Religion Across the Lifeworlds of an Urban Youth. (October 2016) - Skerrett, Allison
This article uses case study methods and theories of literacy as social practice to explore how an adolescent developed her religious identity and religious literacies in relationship with more secular identities and literacy practices across multiple social contexts. It further examines how the youth engaged her religious identity and religious literacies concomitantly with other identities and literacy practices for developing and displaying academic identity and academic literacies in school. In so doing, the article offers important theoretical understandings and pedagogical implications relative to the potential of religious identity and religious literacies in the education of increasingly diverse urban school populations.